2013
DOI: 10.1111/jocn.12352
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of pressure ulcer preventive measures in nursing homes: a comparison of Dutch and German nursing staff

Abstract: Recurring education about pressure ulcer prevention is required among nursing staff employed in Dutch and German nursing homes, particularly in relation to the use of ineffective and outdated preventive measures. Obstacles regarding the implementation of preventive measures should be addressed to achieve a change in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
17
1
3
Order By: Relevance
“…In the USA and some European countries, questionnaire surveys on the knowledge and practices regarding pressure injury prevention have been performed for physicians, nurses, and nursing students in acute care settings. [11][12][13][14] Similar reports from Japan have been published. 15,16 In the home care setting, Fujita et al recently evaluated a questionnaire survey on pressure injury prevention among caregivers at home care and clarified that the levels of knowledge and practice among them were relatively low.…”
Section: Introductionsupporting
confidence: 73%
“…In the USA and some European countries, questionnaire surveys on the knowledge and practices regarding pressure injury prevention have been performed for physicians, nurses, and nursing students in acute care settings. [11][12][13][14] Similar reports from Japan have been published. 15,16 In the home care setting, Fujita et al recently evaluated a questionnaire survey on pressure injury prevention among caregivers at home care and clarified that the levels of knowledge and practice among them were relatively low.…”
Section: Introductionsupporting
confidence: 73%
“…When the literature is examined, it is seen that nurses have a positive attitude towards PUP. [15][16][17][18]30 This study also reveals that only in less than one-fourth of the nurses' attitudes towards PUP were positive.…”
Section: Attitude Of Nurses Toward Pupmentioning
confidence: 57%
“…21,22,29 In the investigations done, the PUP knowledge levels of the nurses were determined to be 79.1%, 73.6%, 50%, 49.6% and 29%, respectively. 17,18,27,29,30 Meesterberends et al (2013) study establish that nurses should improve their knowledge on PUP. 30 Abou El Enein and Zaghloul (2011) and Panagiotopoulou and Kerr (2002) suggest that nurses need to increase their awareness of PUP.…”
Section: Knowledge Of Nurses Toward Pupmentioning
confidence: 97%
See 1 more Smart Citation
“…Gunningberg et al found that knowledge of PU prevention among nursing staff in Sweden was inadequate, specifically with regard to reducing the degree and duration of pressure and shear. Other studies indicate that there is room for improvement regarding knowledge of PU prevention not just among Swedish nurses .…”
Section: Introductionmentioning
confidence: 99%